DETERMINAN PEMILIHAN KARIER SEBAGAI AKUNTAN PUBLIK - Suwitri, Ni Putu Bella Ari; Suartana, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024, 2024)
Career is an important aspect that can direct life and contribute greatly to determining one's life goals. This study aims to determine the effect of motivation, financial rewards, labor market considerations, and professional risk in career interest as a public accountant. The study population is an active student of the 2019 Accounting Program, Faculty of Economics and Business, Udayana University. The sampling technique used was the simple random sampling that was calculated using the slovin formula and getting a sample of 156 respondents. The data collection method used is a questionnaire propagated through Google form by means of multiple linear regression analysis techniques. The results of the study suggest that motivation, financial rewards, employment market considerations have a positive effect, while professional risks have no effect on career interest as a public accountant. This is because accounting students generally do not understand fully the legal risks endured by the public accountant regarding the type of work they do.